Ethical aspects in research con native peoples in America - Cancino-Jiménez, Daniella; Valencia-Contrera, Miguel; Rivera-Rojas, Flérida; Villa-Velasquez, Jenifer (Southern perspective / Perspectiva austral, 2024)
Introduction: Research involving indigenous populations is not exempt from ethical dilemmas during its execution. These populations are susceptible to being compromised, given that each indigenous group possesses its own culture, language, beliefs, and connection to their lands. Such research must navigate challenges such as respect for autonomy, justice, beneficence, and non-maleficence.Objective: To analyze the ethical considerations involved in research with indigenous peoples of the Americas.Methods: A rapid literature review was conducted across scientific databases including PubMed, CINAHL, Web of Science (WOS), and the Virtual Health Library (BVS); in Spanish, English, and Portuguese; with no discrimination regarding the type of study. A total of 668 studies were identified, with the final sample consisting of 13 studies.Results: Ethical concerns have predominantly centered on individual rights, with free, prior, and informed consent being the most frequently compromised aspect. There is a need to protect this process and its application from the perspective of each indigenous group's worldview.Conclusions: It is necessary to develop strategies that are centered on the characteristics of indigenous peoples, including the adaptation and/or expansion of ethical principles in a manner that is coherent and respectful of their beliefs, practices, customs, and health phenomena.